NR3C1 gene polymorphisms are associated with high-altitude pulmonary edema in Han Chinese - Yang, Yingzhong (J Physiol Anthropol, 2019)
BACKGROUND: High-altitude pulmonary edema (HAPE) is a life-threatening form of non-cardiogenic edema which occurs in unacclimatized individuals after rapid ascent to high altitude. NR3C1 gene encodes for glucocorticoid receptor (GR) which plays an important role in stress and inflammation. This study aimed to investigate the association of NR3C1 polymorphisms with the susceptibility to HAPE in Han Chinese. METHODS: The 30 SNPs in the NR3C1 gene were genotyped by the Sequenom MassARRAY SNP assay in 133 HAPE patients (HAPE-p) and 135 matched Han Chinese resistant to HAPE (HAPE-r). The genotypic and allele frequencies, odds ratios (ORs), and 95% confidence intervals (95% CIs) were calculated, respectively. RESULTS: The 12 SNPs showed a significant difference between the HAPE-p and HAPE-r groups. In allelic model analysis, we found that the allele “A” of rs17287745, rs17209237, rs17209251, rs6877893, and rs1866388; the allele “C” of rs6191, rs6188, and rs2918417; the allele “T” of rs33388 and rs4634384; and the allele “G” of rs41423247 and rs10052957 were associated with increased the risk of HAPE. In the genetic model analysis, we found that rs17287745, rs6191, rs6188, rs33388, rs2918417, rs6877893, rs1866388, rs41423247, rs4634384, and rs10052957 were relevant to the increased HAPE risk under the dominant model. In addition, the haplotype AACACTCAAGTG of the 12 SNPs was detected to be significantly associated with HAPE risk (OR = 2.044, 95%CI = 1.339~3.120, P = 0.0008), while the haplotype GGAGCACGACCG was associated with the decreased risk of HAPE (OR = 0.573, 95% CI = 0.333~0.985, P = 0.0422). CONCLUSIONS: Our findings provide new evidence for the association between SNPs in NR3C1 and an increased risk of HAPE in the Chinese population. NR3C1 polymorphisms are associated with the susceptibility to HAPE in Han Chinese. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s40101-019-0194-1) contains supplementary material, which is available to authorized users.